Identification of genetic risk factors in the Chinese population implicates a role of immune system in Alzheimer’s disease pathogenesis - Zhou, Xiaopu; Chen, Yu; Mok, Kin Y.; Zhao, Qianhua; Chen, Keliang; Chen, Yuewen; Hardy, John; Li, Yun; Fu, Amy K. Y.; Guo, Qihao; Ip, Nancy Y. (Proceedings of the National Academy of Sciences - PNAS, 2018)
Alzheimer’s disease (AD) is a leading cause of mortality among the elderly. We performed a whole-genome sequencing study of AD in the Chinese population. In addition to the variants identified in or around the APOE locus (sentinel variant rs73052335, P = 1.44 × 10−14), two common variants, GCH1 (rs72713460, P = 4.36 × 10−5) and KCNJ15 (rs928771, P = 3.60 × 10−6), were identified and further verified for their possible risk effects for AD in three small non-Asian AD cohorts. Genotype–phenotype analysis showed that KCNJ15 variant rs928771 affects the onset age of AD, with earlier disease onset in minor allele carriers. In addition, altered expression level of the KCNJ15 transcript can be observed in the blood of AD subjects. Moreover, the risk variants of GCH1 and KCNJ15 are associated with changes in their transcript levels in specific tissues, as well as changes of plasma biomarkers levels in AD subjects. Importantly, network analysis of hippocampus and blood transcriptome datasets suggests that the risk variants in the APOE, GCH1, and KCNJ15 loci might exert their functions through their regulatory effects on immune-related pathways. Taking these data together, we identified common variants of GCH1 and KCNJ15 in the Chinese population that contribute to AD risk. These variants may exert their functional effects through the immune system.